Design and Synthesis of Capacitance Multiplier Using LT1228s and a Grounded Capacitor - Channumsin, Orapin; Roongmuanpha, Natchanai; Likhitkitwoerakul, Nutcha; Tangsrirat, Worapong (My University, 2026)
In this study, the design and synthesis of a grounded capacitance multiplier is discussed. The proposed circuit consists of two commercially available integrated circuits (ICs) named LT1228, together with a single grounded capacitor as a passive element. The transconductance gain of LT1228 allows for electronic control of the simulated equivalent capacitance value. The LT1228 transconductance gain is easily adjusted through the external bias current, which has a wide adjustable range of 1 µA to 1 mA. No component matching is required for the designed simulator. A non-ideal analysis of the proposed circuit has been investigated in detail. The workability of the proposed circuit and its application example as a first-order lowpass filter has been confirmed with the theoretical findings through PSPICE software. The results indicate that the proposed simulator has excellent performance and matches the theory.
Keywords: Capacitance multiplier; Commercially available integrated circuit; Electronically controllable; LT1228